An Analysis of Independent Clauses and Dependent Clauses in the Lyrics of One Last Time by Ariana Grande - Tarigan, Hery Reynaldi; Purba, Rahel Satri; Siboro, Riby Astri; Sari, Rani Puspa; Silaban, Monika Nalalian; Anita Sitanggang (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the syntactic structure of Ariana Grande’s song “One Last Time” by analyzing independent and dependent clauses used throughout the lyrics. The research aims to identify the types of clauses and their functions in conveying emotional meaning. Using a qualitative descriptive method, 71 clauses were identified, including 45 independent clauses and 26 dependent clauses. The independent clauses express direct emotions, intentions, and realizations, while the dependent clauses provide reasoning, elaboration, and emotional depth. Recurrent syntactic patterns, such as noun and adverbial clauses, support the emotional narrative of the song. The findings reveal how grammatical structures enhance the emotional intensity and coherence of the lyrics. This study highlights the significant role of clause types in shaping lyrical meaning and stylistic expression.